(9/7z)+(3/z)=1

Simple and best practice solution for (9/7z)+(3/z)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9/7z)+(3/z)=1 equation:


D( z )

z = 0

z = 0

z = 0

z in (-oo:0) U (0:+oo)

(9/7)*z+3/z = 1 // - 1

(9/7)*z+3/z-1 = 0

9/7*z^1+3*z^-1-1*z^0 = 0

(9/7*z^2-1*z^1+3*z^0)/(z^1) = 0 // * z^2

z^1*(9/7*z^2-1*z^1+3*z^0) = 0

z^1

(9/7)*z^2-z+3 = 0

(9/7)*z^2-z+3 = 0

DELTA = (-1)^2-(3*4*(9/7))

DELTA = -101/7

DELTA < 0

z in { }

z belongs to the empty set

See similar equations:

| 6x-4=5x+18 | | -4(-7+4r)=-28-8r | | 6x-4=5x-18 | | 6x+4=5x-18 | | 18+5y= | | 6(8-n)=28-n | | 99x-8=55 | | 6x+4=5x+18 | | 18+5y+7+3y+5y+2y= | | 5(y+4)=3(x-2) | | -4(n-5)+3n=10-3n | | 2ix^2+x+3i=0 | | 7x-6=-22 | | -18-6x=-6(5x-2)-6x | | -18-6x=6(5x-2)-6x | | y=6/8+1 | | -2/7*3 | | 1/2(-6m) | | -5=-2-7 | | m^2+7m+8=0 | | 5.5x+9-9.5x=5 | | 253t-16t^2=151 | | (-3/(2y-10))+4=-5/(y-5) | | 4x+15y=15 | | 9m^2+63m+72=0 | | -2-10=7x+15-6x | | e^4x=7.42 | | 3t^3+8t^2+4t=0 | | -0.10(51)+0.75x=0.05(x-18) | | -2i(5+i)=0 | | -27p-6(2-6p)=4(p-6)-3 | | sqrt(9x^3y^5)= |

Equations solver categories